Cover Image. Issue 9 (21st May 2020) - Zhang, Feifei; Li, Weikai; Li, Huiru; Gao, Shaobing; Sweeney, John A.; Jia, Zhiyun; Gong, Qiyong
Abstract : COVER ILLUSTRATION Jet lag is an exogenous circadian rhythm disorder following long‐distance air travel across multiple time zones. The present intrinsic whole brain functional connectivity analyses demonstrate that the nodal efficiency and centrality were lower mainly in the thalamus (illustrated as light blue in the brain), and the disrupt thalamocortical circuits (as shown in the color connections between thalamus and precentral gyrus, paracentral gyrus, temporal gyrus, postcentral gyrus, occipital gyrus, and subcortical nuclei) during jet lag.